Effect of different single and combined antihypertensive drug regimens on the mortality of critical care patients - Fang, Yipeng; Huang, Xianxi; Shi, Junyu; Ren, Chunhong; Zhang, Xin (Frontiers in Pharmacology, 2024)
Objective: To investigate the effect of different single and combined pre-admission antihypertensive drug regimens on the prognosis of critically ill patients.We performed a retrospective cohort study using data from the Medical Information Mart for Intensive Care-IV (MIMIC-IV) database. All initial ICU admission records of patients with hypertension and previous antihypertensive exposure before ICU admission were included. Our primary outcome was 90-day mortality. Propensity score matching (PSM) and inverse probability of treatment weighting (IPTW) were used to balance the distribution of baseline characteristics. Logistic regression analysis and subgroup analysis were performed to determine the independent effect of different single and combined antihypertensive drug regimens on 90-day mortality.Results: A total of 13,142 patients were included in the final analysis. The 90-day mortality rate in the combined groups is lower than that in the single therapy group (10.94% vs. 11.12%), but no statistical significance was found in the original cohort (p = 0.742). After adjustment for potential confounders, the significantly decreased 90-day mortality rate was found in the combined groups (10.78% vs. 12.65%, p = 0.004 in PSM; 10.34% vs. 11.90%, p = 0.007). Patients who were exposed to either ACEIs or ARBs had a better prognosis than those not exposed (7.19% vs. 17.08%, p < 0.001 in single antihypertensive groups; 8.14% vs.18.91%, p < 0.001 in combined antihypertensive groups). The results keep robustness in the PSM and IPTW cohorts. In the logistic regression model analysis, combined therapy was associated with a 12% to 20% reduced risk of 90-day death after adjusting potential confounders (OR 0.80-0.88, all p < 0.05), while exposure to ACEIs or ARBs was associated with the decreased risk of 90-day death by 52%-62% all p<0.001) and 40%-62% (OR 0.38-0.60, all p<0.001) in the single and combined therapy groups, respectively. The results were still robust to subgroup analysis.Conclusions: Pre-admission combined antihypertensive therapy is associated with a significantly lower risk of death than exposure to single antihypertensives in critically ill patients. Meanwhile, either ACEIs or ARBs seem to be the optimal candidates for both single and combined therapy. Further high-quality trials are needed to confirm our findings.